Hepatitis C virus infection induces elevation of CXCL10 in human brain microvascular endothelial cells. Issue 9 (8th March 2016) - Liu, Yuan; Chen, Li; Zou, Ziying; Zhu, Bing; Hu, Zonghai; Zeng, Ping; Wu, Lijuan; Xiong, Jie
Abstract : Hepatitis C virus (HCV) primarily infects liver tissues, while pathogenesis of extrahepatic tissues has been reported. About 50% of patients with HCV infection suffer from neurological disease. The underlying molecular mechanisms remain unclear. In the present study, we aimed to investigate the induction of CXC chemokine ligand 10 (CXCL10) in human brain microvascular endothelial cells (HBMECs) by HCV infection. CXCL10 and its receptor CXCR3 were constitutively expressed in HBMECs. HCV infection induced CXCL10 elevation in HBMECs. The elevation of CXCL10 in HBMECs was eliminated when HCV infection was blocked by neutralizing antibodies. NF‐κB is a positive regulator for CXCL10 transcription. HCV infection led to an increased phosphorylation of NF‐κB (ser536) in HBMECs, and CXCL10 induced by HCV was slightly decreased when an inhibitor of NF‐κB was added. IL1 beta and IFN gama were also upregulated in HCV infected HBMECs, and could be depressed by inhibitor of NF‐κB. Thus, HCV infection leads to upregulated expression of CXCL10 in HBMECs, which is probably via the phosphorylation of NF‐κB. The findings of this study provide potential mechanisms and novel targets for HCV induced neuroinflammation. J. Med. Virol. 88:1596–1603, 2016 . © 2016 Wiley Periodicals, Inc.